The Urgency of Developing a Four-Tier Diagnostic Test Instrument and Its Validity - Hidayatul Aula Hardiyanti; Novia Ayu Sekar Pertiwi; Ino Anga Putra; Kartika Wulandari (SCHOOLAR: Social and Literature Study in Education, 2026)
A valid diagnostic test instrument is an important component in accurately identifying student misconceptions. This study aims to examine the urgency and validity of the Four-Tier diagnostic test instrument on temperature and heat. The method used is research and development (R&D) with the Borg & Gall model adapted from Sugiyono. The validity of the instrument was tested through assessments by material experts and learning evaluation experts using a four-point Likert scale. The results showed that all test items received good to excellent categories, indicating that the instrument has adequate content and construct validity. These findings confirm that a valid Four-Tier diagnostic test instrument can be a reliable tool in uncovering student misconceptions in physics learning.